The association between obesity and gynecological cancer - Yin-Hsun Feng (Wolters Kluwer Medknow Publications, 2015)
Obesity is a growing problem and has significant implications for a variety of diseases, including human cancers. A positive association between obesity and incidence of many gynecological cancers, including endometrial cancer, ovarian cancer, and breast cancer has been observed. The mechanism proposed to connect obesity and these cancers was sex hormone, insulin resistance, and certain adipokines. Obesity adversely affects survival in most studies. For endometrial cancer, the obesity was associated with increased risk and unfavorable outcome. With regard to ovarian cancer and cervical cancer, the evidence was inconsistent. The positive association between obesity and the risk of postmenopausal breast cancer has been consistently observed but it is not the same story in premenopausal breast cancer. But the prognosis for both pre- and postmenopausal breast cancer was substantially worse among obese than normal-weight individuals. In this article, we review the current evidence linking obesity with risk and outcome of gynecological cancers.